Overview of Design Development of FCC-hh Experimental Interaction Regions - Seryi, A; Abelleira Fernandez, J; Cruz Alaniz, E; van Riesen-Haupt, L (Joint Accelerator Conferences Website, 2017)
The experimental interaction region (EIR) is one of the key areas that define the performance of the Future Circular Collider. In this overview we will describe the status and the evolution of the design of EIR of FCC-hh, focusing on design of the optics, energy deposition in EIR elements, beam-beam effects and machine detector interface issues.